Návrh motivačního programu firmy - Bartoš, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato bakalářská práce analyzuje problémy firemního klimatu, přesněji motivačního programu pro zaměstnance. Obsahuje návrh motivačního programu, který by zvýšil efektivnost a prosperitu firmy na trhu skrze spokojenost zaměstnanců.

Bachelor thesis analyses problems of company clime, exactly motivational system for employee. It includes the proposal of motivational system, which would raise effectiveness of the company and prosperity of the company in the marketplace through the satisfaction of the employees.
Motivation Program of Company
Keywords: motivační program; motivace; stimulace; systém odměn; firemní klima; motivational system; motivation; stimulation; system of reward; company clime